Shenkang injection combined with alprostadil for chronic renal failure: A systematic review and meta-analysis - Xie, Feng; Zhang, Tiantian; Zhang, Pu; Qu, Xinliang; Li, Min; Lan, Wei (Frontiers in Medicine, 2023)
Abstract Objective: Systematic evaluation of the clinical efficacy and safety of Shenkang injection combined with alprostadil in the treatment of chronic renal failure. Methods: We searched 7databases, including CNKI, Wanfang database, VIP, CBM, PubMed, Embase and Cochrane Library and investigated the randomized controlled trial (RCT) of Shenkang injection combined with alprostadil in the treatment of chronic renal failure. The search time range is from 2012 to present. revman5.2 software was used to analyze the results of the data, and the quality of the included literature was evaluated according to the Cochrane risk of bias tool.Results:A total of 20 RCTs with 1573 patients were included. The results of meta-analysis show that the experimental group is better than the control group in improving the total effective rate, Creatinine clearance rate (Ccr) and Aromatase (ArE) levels, and reducing the patients' Serum creatinine (Scr), Urine protein quantification (Upro) and Blood urea nitrogen (BUN)levels. There are statistical differences between the two groups. Conclusion:Shenkang injection combined with alprostadil has a certain curative effect in the treatment of chronic renal failure, and there are fewer adverse reactions. However, this conclusion needs more clinical studies to further verify.